Pancasila sebagai sistem etika dan instrumen pendidikan karakter mahasiswa dalam era globalisasi - muda, raditya ariesta (Maliki Interdisciplinary Journal, 2025)
This study examines how Pancasila can function both as an ethical system and as an instrument for character education among university students amid the increasingly complex challenges of globalization. The novelty of this research lies in its analytical approach, which integrates the ethical perspectives of Pancasila with the character needs of 21st-century students. The aim of the study is to explain the role of Pancasila values in shaping students who are ethical, adaptable, and firmly grounded in national identity. This research employs a qualitative literature review by analyzing books, scholarly journals, and educational policies. The findings indicate that Pancasila remains relevant as a guide for ethics and character formation, yet its implementation faces significant challenges from global cultural currents and digital technologies. The study recommends strengthening Pancasila-based character education through university curricula, experiential learning, and the integration of technology grounded in core values. (Suprayogo, 2016)